Influence of specimen size and sheet thickness on the material behavior of AZ31B under uniaxial tension - Suttner, Sebastian; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2016)
Concerning a low specific density, magnesium alloys offer a great potential to reduce the part weight. Due to the conditional formability of magnesium alloys at room temperature, forming processes are mostly realized at elevated temperatures. Within this contribution, uniaxial tensile tests for two different specimen geometries with a gauge length of 50 mm and 2 mm and a cross section of 12.5×1 mm2 and 2×1 mm2 are carried out for the magnesium alloy AZ31B at an elevated temperature of 200 °C. Since the specimen size is reduced, the influence of the sheet thickness needs to be analyzed. The analysis of the sheet thickness results in a change of the determined flow curve above a strain level of 0.1 and a much earlier failure of specimen with an initial sheet thickness of 1.5 mm. The changed material behavior can be explained by a different microstructure, e.g. the influence of the grain size. In summary, a characterization of the magnesium alloy AZ31B at elevated temperatures can be realized with a miniaturized test setup.
LFT Import::2019-07-29 (2212)